Analysis of internal control models - Simonaitytė, Živilė (Buhalterinės apskaitos teorija ir praktika, 2014)
Internal control evaluation is one of the most important steps of audit. For conducting this step properly internal control evaluation models are used. Every model has its own advantages and disadvantages. Pros and cons of the most popular internal control models, audit standards used in the biggest countries of the world, researches in the field of effective internal control evaluation are analysed in this article. Structure of internal control evaluation is provided. It enables to connect advantages and dilute disadvantages of the most commonly used internal control evaluation models.